2021
DOI: 10.1099/jmm.0.001347
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to nitrofurantoin is an indicator of extensive drug-resistant (XDR) Enterobacteriaceae

Abstract: Introduction. Nitrofurantoin is one of the preferred antibiotics in the treatment of uropathogenic multidrug-resistant (MDR) infections. However, resistance to nitrofurantoin in extensively drug-resistant (XDR) bacteria has severely limited the treatment options. Gap statement. Information related to co-resistance or collateral sensitivity (CS) with reference to nitrofurantoin resistant bacteria is limited. Aim. To study the potential of nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Furthermore, 4.05% (3/74 isolates) of the strains were categorized as XDR isolates; remarkably, all the strains presented a nitrofurantoin-resistant pattern. This is consistent with Khamari et al (2021) [68], who reported that resistance to nitrofurantoin indicates the underlying extensively drug-resistant (XDR) phenotype in Enterobacteriaceae, which could complicate the treatment of UTIs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, 4.05% (3/74 isolates) of the strains were categorized as XDR isolates; remarkably, all the strains presented a nitrofurantoin-resistant pattern. This is consistent with Khamari et al (2021) [68], who reported that resistance to nitrofurantoin indicates the underlying extensively drug-resistant (XDR) phenotype in Enterobacteriaceae, which could complicate the treatment of UTIs.…”
Section: Discussionsupporting
confidence: 90%
“…This is in contrast to our study, where the F group was one of the most prevalent phylogroups (14.9%). These differences in the prevalence of the phylogenetic groups reported in different studies may be explained by differences in sampling location, health status, dietary and host genetic factors, and host social conditions [68,69].…”
Section: Discussionmentioning
confidence: 93%
“…Nitrofurantoin was not widely used in the population under study (3.5%), but it showed the highest resistance across sexes and age groups. Nitrofurantoin resistance is a marker of extensive drug resistance in Enterobacteriaceae, a family challenging to treat 30 but not seen in our findings. Last, ceftriaxone was administered a fifth of the time in the ED, but two-thirds of the uropathogens showed resistance.…”
Section: Discussionmentioning
confidence: 41%
“…There are several genetic mechanisms that confer F resistance, including chromosomally mediated mutations in nfsA, nfsB, and ribE proteins, as well as plasmid-mediated multiple drug efflux pumps that encode by oqxAB genes [50]. Available at www.veterinaryworld.org/Vol.15/June-2022/14.pdf Therefore, F resistance may represent an indicator of extensive antibiotic resistance in enteric bacteria [51]. Despite the infrequent use of C in poultry farming in Iraq, about 60% of the present isolates showed resistance to this antibiotic.…”
Section: Discussionmentioning
confidence: 99%